PENGARUH MEDIA ANIMASI TERHADAP PEMBELAJARAN TEKNIK DASAR DRIBBLING - Rohmad Aprianto; Dwi Adi Nugroho; Nurman Rahmadhan (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2017)
Football is one of the most popular sports for people around the world. This sport is very universal, besides being favored by men this sport is also favored by women not only young and old children. In the fourth grade of SDN 01 Banyuputih Kalinyamatan Jepara, all of the students liked soccer but students in doing so still made many mistakes, especially in the basic dribbling technique where dribbling is one of the most important basic techniques in the sport. In this increasingly modern era, children or students are more inclined to like things that smell of technology, so it requires a more modern teaching media to attract interest in learning. Animation is one of the media that can be used in learning to replace the media image that is considered less effective because it is difficult to understand. This research is a classroom action research conducted directly by the teacher concerned or the researcher. This research was conducted in two cycles, each of which consisted of two meetings. In cycle 1 there are some students who have not completed as much as 44% of 25 students, because students are less interested in the learning media used. While in cycle 2 there were 24% of 25 students who were not finished because there were still mistakes when dribbling.